2021
DOI: 10.1177/14771535211008179
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of adaptive control on the LED street luminaire lifetime and on the lifecycle costs of a lighting installation

Abstract: We report for the first time the effect of ageing due to adaptive control of lighting on the lifecycle costs of luminaire installations. Two types of LED street luminaire were aged (1) as the luminaire lit for 9 hours and then switched off for 3 hours and (2) under intensive ageing using adaptive control conditions mimicking presence of vehicles, where the luminaires were switched with 30-second interval between 100% and 20% power within the cycle of (1). The test continued for 32,000 hours. Luminaire lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The LED lamps are quite resistant to frequent switching, ensuring consistent performance and reliability over time. In fact, the first definite observation of reduced lifetime due to switching was observed only recently in natural ageing conditions [58].…”
Section: Temporal Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The LED lamps are quite resistant to frequent switching, ensuring consistent performance and reliability over time. In fact, the first definite observation of reduced lifetime due to switching was observed only recently in natural ageing conditions [58].…”
Section: Temporal Characteristicsmentioning
confidence: 99%
“…Significant energy and cost savings can be obtained with LED lighting when light is used only when needed in buildings, pedestrian areas, and streets [59][60][61]. Figure 4 shows a comparison of streetlamp ageing results, when one lamp group has natural ageing while another cycled group of lamps has been switched between 20% and 100% power with 30 s interval [58]. Although after 10 000 h of ageing the cycled group shows a few percent lower luminous flux, the switching frequency is about ten times the average switching frequency which would occur in real traffic conditions with smart lighting.…”
Section: Temporal Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…LED lighting already brings significant efficiency improvements over conventional lighting without intelligence and computing. Askola et al [88] revealed that LED lighting had become an essential driver in the industry in recent years. There is a massive potential for savings when replacing conventional exterior lights with LED lights.…”
Section: Smart Lighting Technologies 1) Led Lightingmentioning
confidence: 99%